Computational identification and characterization of putative miRNAs in Heliothis virescens - Chilana, Poonam (Biomedical Informatics, 2013)
Heliothis virescens, a polyphagous pest, is one of the most destructive pests of many crops and vegetables. Various insecticides and pesticides are used by agriculturalists to stop the growth and development of this pest. RNA interference is a new area for the management of pests/insects by inhibiting the growth related RNAs. This involves the miRNAs identification and its characterization. In the present study, computational approach is applied to predict putative miRNA candidates along with their possible target(s) in the Heliothis virescens. A total of 63,662 ESTs were downloaded from dbEST database and processed, trimmed and masked through EGassembler. The H. virescens contigs database obtained after assembly was now used to find the putative miRNA candidates by performing a local BLAST with the miRNAs of insects retrieved from miRBase. We have predicted putative miRNA candidates by homology search against all the reported insect miRNAs. These putative miRNAs candidates were further validated and filtered by different features. In addition, we have also attempted to predict the putative targets of these filtered miRNAs, by making use of 3' untranslated regions of mRNAs from B. mori. These miRNAs and their targets in H. virescens will help in improved understanding of molecular mechanisms of miRNA and development of novel and more precise techniques for better understanding some post transcriptional gene silencing.